HealthSpot: Analysis of a Bankruptcy in Kiosk-based Telehealth - Mudumba, Rajeev (Telehealth and Medicine Today, 2018)
HealthSpot, Inc., the kiosk-based telehealth services provider founded in Dublin, Ohio in 2010 had raised about 46.7 million in several rounds of venture funding and debt capital since its inception. Among its funders, Xerox aspired to combine its BPO (business process outsourcing) knowledge with HealthSpot’s software platform and also serve as HealthSpot’s BPO provider. HealthSpot went on to find other partners: MetroHealth; Mayo Health; Kaiser Permanente; the Cleveland Clinic, and University Hospitals; and Rite Aid (the third largest retail drugstore chain in the country) among others. But, despite the capital it raised and the name brand partners it brought together, HealthSpot closed up shop in December 2015.